Co-decode algorithm of network coding with hardware logic - Hui LI; Ming-long ZHANG; Fu-xing CHEN; Han-xu HOU; Kai PAN; Wei WANG; Hu-sheng YUAN; Tao SUN (Tongxin Xuebao, 2012)
Practical general coder and decoder of network coding(NC)with HDL(hardware description language)logic for wire-speed nodes was presented.The NC coders applied random linear network coding (RLNC) and the decoders recovered the original packets by Cramer’s rule.The structures and algorithms of NC coder and decoder were designed in detail and implemented in HDL with NetFPGA boards.Comparing with traditional stored-and-forward mechanism,network emulations showed that networks with wire-speed NC coder and decoder nodes could achieve the capacity bound of max-flow min-cut theorem,and the end-to-end delay was guaranteed on a small constant.